Efficiency Improvement in Assembly Rubber Wooden Toys Using Motion and Time Study and Principles of Ergonomics: A Case Study of a Sample Factory: 1 Faculty of Engineering, Rajamangala University of Technology Srivijaya, 2 Faculty of Engineering, Princess of Naradhiwas University - Rawangwong, Surasit; Homkhiew, Chatree; Sani, Suhaidee; Rodjananugoon, Julaluk; Tehyo, Muhamad (Princess of Naradhiwas University Journal, 2019)
The objective of this research was to study a assembling process of rubber wooden camera toy using time and motion study and ergonomics principles. From the investigation of the toy assembling process, it was low assembling efficiency because the assembling procedure and working motions were inappropriate which affected the exuasted workers and waste time in the process. Thus, the researcher applied the time-motion study, ECRS technique and ergonomics method to improve the operating procedure and also design the ergonomical tables and chairs. After the process improved, the number of assembly processes was reduced from 8 steps to 7 steps and the standard assembling times was also reduced from 3.254 minutes/piece to 2.508 minutes/piece (0.746 minute/piece reduction). Moreover, the efficiency of assembling process increased 25.96 percent. In case of the working motions, after the ergonomics assessment with RULA method and fatigue survey, the risks in assembling process can be reduced to the satisfactory level.